SP-RF-ARIMA: A sparse random forest and ARIMA hybrid model for electric load forecasting - Kamran Hassanpouri Baesmat; Farhad Shokoohi; Zeinab Farrokhi (Global Energy Interconnection)
Accurate Electric Load Forecasting (ELF) is crucial for optimizing production capacity, improving operational efficiency, and managing energy resources effectively. Moreover, precise ELF contributes to a smaller environmental footprint by reducing the risks of disruption, downtime, and waste. However, with increasingly complex energy consumption patterns driven by renewable energy integration and changing consumer behaviors, no single approach has emerged as universally effective. In response, this research presents a hybrid modeling framework that combines the strengths of Random Forest (RF) and Autoregressive Integrated Moving Average (ARIMA) models, enhanced with advanced feature selection—Minimum Redundancy Maximum Relevancy and Maximum Synergy (MRMRMS) method—to produce a sparse model. Additionally, the residual patterns are analyzed to enhance forecast accuracy. High-resolution weather data from Weather Underground and historical energy consumption data from PJM for Duke Energy Ohio and Kentucky (DEO&K) are used in this application. This methodology, termed SP-RF-ARIMA, is evaluated against existing approaches; it demonstrates more than 40% reduction in mean absolute error and root mean square error compared to the second-best method.